2004
DOI: 10.1074/jbc.m401058200
|View full text |Cite
|
Sign up to set email alerts
|

Wounding Induces Motility in Sheets of Corneal Epithelial Cells through Loss of Spatial Constraints

Abstract: Cellular responses to wounding have often been studied at a molecular level after disrupting cell layers by mechanical means. This invariably results in damage to cells at the edges of the wounds, which has been suggested to be instrumental for initiating wound healing. To test this, we devised an alternative procedure to introduce gaps in layers of corneal epithelial cells by casting agarose strips on tissue culture plates. In contrast to mechanical wounding, removal of the strips did not lead to detectable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(161 citation statements)
references
References 47 publications
11
150
0
Order By: Relevance
“…These observations are compatible with those dealing with corneal epithelia (11) or endothelial cells (12) in the sense that a true injury of the border cells is not necessary to trigger the migration of these cells. This conclusion validates the underlying assumption of many studies dealing with in vitro wound healing.…”
Section: Migration Triggered By a Model Wound And Advantages Of The Asupporting
confidence: 77%
“…These observations are compatible with those dealing with corneal epithelia (11) or endothelial cells (12) in the sense that a true injury of the border cells is not necessary to trigger the migration of these cells. This conclusion validates the underlying assumption of many studies dealing with in vitro wound healing.…”
Section: Migration Triggered By a Model Wound And Advantages Of The Asupporting
confidence: 77%
“…HB-EGF release has been detected in a number of systems including acute renal injury and wounded keratinocytes (Sakai et al, 1997;Tokumaru et al 2000). The use of functional blocking antibodies inhibited the responses induced by this release (Shah et al 2004, Block et al 2004, Xu et al 2004. In our system HB-EGF blocking antibody inhibited wound induced EGFR phosphorylation ( Figure 3).…”
Section: Discussionmentioning
confidence: 64%
“…A number of investigators have shown that stimulation of GPCRs leads to release of HB-EGF and activation of the EGFR (Block et al, 2004;Pierce et al, 2001;Prenzel et al, 1999;Schafer et al 2004b;Shah et al 2004). Activation of the GPCRs can stimulate the ADAM family of matrix metalloproteases that release the EGFR ligands (Fischer et al, 2004;Yan et al, 2002;Schafer et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…A particularly intriguing study on mammalian cells has shown that the activation of EGFR occurs upon the generation of a free edge in the absence of cell damage (Block et al, 2004). Such activation through EGFR depends on the heparin-binding, epidermal growth factor-like, growth factor (HB-EGF) pathway.…”
Section: Discussionmentioning
confidence: 99%